2012
DOI: 10.1177/1354856511430184
|View full text |Cite
|
Sign up to set email alerts
|

Interactivity on Swedish newspaper websites: What kind, how much and why?

Abstract: This article examines what kind of interactive features are available on the websites of Swedish newspapers, and what factors seem to influence the utilization of those features. Using Chung's typology of interactive features, we can discern four types: human (features that facilitate interpersonal communication), human-medium (allowing users to express their personal opinions), medium (allowing users choice options in experiencing news stories) and medium-human (allowing users to customize news to their likin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 54 publications
(72 reference statements)
0
31
0
1
Order By: Relevance
“…These can broadly be classified as either functional studies (Kenney et al 1999;Rosenberry 2005;Shultz 1999;Tankard and Ban 1998), concerned with how interactive elements in online news are presented; and perceived studies (Chung 2007;Larsson 2012) concerned with how interactivity is understood by the audience.…”
Section: The Rise Of Interactive Online Journalism Studiesmentioning
confidence: 99%
“…These can broadly be classified as either functional studies (Kenney et al 1999;Rosenberry 2005;Shultz 1999;Tankard and Ban 1998), concerned with how interactive elements in online news are presented; and perceived studies (Chung 2007;Larsson 2012) concerned with how interactivity is understood by the audience.…”
Section: The Rise Of Interactive Online Journalism Studiesmentioning
confidence: 99%
“…However, this result may be due to the cross-sectional Interestingly, routine rigidity is not found to be influenced by gender, age, or journalistic generation, although this is suggested by previous research (Larsson, 2012;Ryfe, 2009). Solely managerial responsibility among the measured demographic variables leads to overcoming routine rigidity for process-related, cross-channel convergence.…”
Section: To What Extent Are Journalists' Innovative Values Related Tomentioning
confidence: 53%
“…Therefore, only when journalists did not previously invest much in a certain routine, which may be the case with How structural multi-platform newsroom features and innovative values alter journalistic cross-channel and cross-sectional working procedures FINAL PROOF Page 7 of 32 younger and less experienced journalists (Ryfe, 2009, p. 679), have traditional routines been followed less rigidly. In this manner, newspapers with younger web staff also offer more interactive features on their websites (Larsson, 2012).…”
Section: Multi-platform Strategy and Routine Rigiditymentioning
confidence: 99%
“…The study concluded that the analysed newspapers are still in a stage of preinteractivity (Fortunati et al, 2010: 58), showing again a major gap between interactivity as a potential and its spread in practice. Another more recent study (Larsson, 2012) -although limited only to Swedish newspaper venue -provides a deeper insight in the structural factors that either limit or stimulate the interactive features of online news websites. His findings suggest that the most interactive newspaper websites within Swedish context belong to large, national companies with younger staff (Larsson, 2012: 206).…”
Section: Production-and Journalist-centred Perspectivesmentioning
confidence: 99%
“…These responses of the audience and the interaction with the readers are the crucial elements of the news environment, and they have brought about a cultural transformation in journalism. The implications of this core feature of online or digital journalism reach far and wide: online interactivity is argued to challenge the most rudimentary journalistic practices (Boczkowski and Mitchelstein, 2012;Hermida, 2010;Domingo and Paterson, 2011;Singer et al, 2011;Larsson, 2012;Ramirez et al, 2016). The process of news production, the selection of news issues and news sources, and the active response to media contents are increasingly structured around audience behaviour and their personalised preferences.…”
mentioning
confidence: 99%